Convenient and General Synthesis of C-3-Substituted Het(aryl)indole C-Nucleoside Analogues from Sugar Alkynes - Zhou, Xiang; Cao, Zhaoxin; Chen, Qianxia; Zhang, Fuyi; Zhao, Yufen (Synthesis, 2022)
The synthesis of C-3-substituted het(aryl)indole C-nucleoside analogues bearing structurally diverse sugar moieties has been achieved by Sonogashira coupling of terminal sugar alkynes with het(aryl) iodides followed by heteroannulation of the corresponding sugar/het(aryl) alkynes with substituted 2-iodoanilines. This method is simple and general and is suitable for structurally diverse sugars and various het(aryl) iodides. The terminal sugar alkynes include furanosides, pyranosides, and acyclic sugars with sensitive groups and bulky substituents. The het(aryl) iodides involve iodobenzene, iodothiophene, iodobenzothiophene, and iodobenzofuran. Thirty-one examples are presented and the corresponding 2-het(aryl)indole C-nucleoside analogues are obtained in moderate to excellent yields.
Keywords: C-3 substituted het(aryl)indole; C-nucleoside; analogue; sugar alkyne; heteroannulation